MLA Handbook for Writers of Research Papers - Gibaldi, Joseph and Achtert, Walter S. (New York The Modern Language Association of America, 1989)
The MLA Handbook for Writers of Research Papers, incorporating MLA style guidelines, serves as a supplementary text in writing courses or as a reference book for students to use independently. The extraordinary publication success of the first two editions of the Handbook throughout the United States, Canda, and other countries (Japanese translations appeared in 1980 and 1984) testifies to the continuing need for such a teaching and research tool.
Keywords: Writing